High expression of MnSOD promotes survival of circulating breast cancer cells and increases their resistance to doxorubicin - Fu, Afu (2017)
Understanding the survival mechanism of metastatic cancer cells in circulation will provide new perspectives on metastasis prevention and also shed new light on metastasis-derived drug resistance. In this study, we made it feasible to detect apoptosis of circulating tumor cells (CTCs) in real-time by integrating a fluorescence resonance energy transfer (FRET)-based caspase sensor into one in vitro microfluidic circulatory system, and two in vivo models: zebrafish circulation and mouse lung metastatic model. Our study demonstrated that fluid shear stresses triggered apoptosis of breast cancer cells in circulation by elevating the mitochondrial production of the primary free radical, superoxide anion. Cancer cells with high levels of manganese superoxide dismutase (MnSOD) exhibited stronger resistance to shear force-induced apoptosis and formed more lung metastases in mice. These metastasized cells further displayed higher resistance to chemotherapeutic agent doxorubicin, which also generates superoxide in mitochondria. Specific siRNA-mediated MnSOD knockdown reversed all three phenotypes. Our findings therefore suggest that MnSOD plays an important integrative role in supporting cancer cell survival in circulation, metastasis, and doxorubicin resistance. MnSOD can serve as a new biomarker for identifying metastatic CTCs and a novel therapeutic target for inhibiting metastasis and destroying doxorubicin-resistant breast cancer cells.